Perlindungan Hukum Terhadap Pekerja Migran Indonesia di Luar Negeri - Yadila, Natasya; Elia Julio, Christopher; Wicaksana, Dika Hikmah; Pranitiaz, Laras Medina (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The 1945 Constitution of the Republic of Indonesia guarantees equal rights and opportunities for all citizens to obtain employment and a decent livelihood. The lack of job opportunities within the country has driven many Indonesians to seek employment abroad as migrant workers. The Indonesian government strives to protect the rights of migrant workers through various policies and laws, including Law No. 39 of 2004 and Law No. 18 of 2017 on the Protection of Indonesian Migrant Workers.This study aims to examine the legality and legal protection for Indonesian migrant workers abroad. The method used is normative legal research with an analysis of primary, secondary, and tertiary legal materials. The results indicate that although the number of migrant workers has significantly increased in recent years, many are unaware of the legal procedures and fall victim to exploitation and human rights violations.The legal protection provided encompasses various aspects, such as basic rights, safety, health, wages, and social security. These protection principles are based on the principles of integration, equal rights, recognition of human dignity, democracy, social justice, gender equality, non-discrimination, anti-human trafficking, transparency, accountability, and sustainability. To enhance the effectiveness of protection, it is necessary to increase legal awareness and compliance with legal procedures by both migrant workers and related institutions